Does Fifth Industrial Revolution Benefit or Trouble the Global Civil Society? - Costa, C. M.; Leandro, F.; Martínez-Galán, E. (Contestations in Global Civil Society, 2022)
The United Nations recognizes “civil society” as the “third sector” of society, along with public (governmental) and private sector organizations. The term global “third sector” comprises the worldwide reach of civil society organizations (CSOs). In this chapter, we discuss how technological advancements could influence global civil society. Humans and machines will increasingly interact and collaborate closely in the future. The Industry Revolution (IR) 5.0 brings new challenges, such as Artificial Intelligence (AI) and machine learning, which pose significant opportunities but also important risks to the role of CSOs. Regarding opportunities, it can be highlighted the potential of the IR 5.0 to better work with big data and to increase knowledge in support of the participation of CSOs in global governance and debates, more precisely by increasing their capabilities in knowledge production and practical implementation. One example is the role of AI in making sense of the large volume of data recorded by satellites, drones, and sensors throughout the planet to better inform environmental policies and debates. Risks are also significant, particularly for an incipient and pioneering technology that takes time for the governance systems to understand and regulate. Another example is the misuse of technology and algorithms to generate targeted misinformation and propaganda to influence public opinion and elections. Governments around the world and leading high-tech companies should define a framework that regulates IR 5.0. Global civil society could play an important role in demanding and lobbying the creation of this framework. For this goal, CSOs need to understand how stakeholders see and adapt to technological challenges.